Considering the effect of optical attenuation on photon-enhanced thermionic emission converter of the practical structure - Huang Shanfeng (De Gruyter, 2021)
Photon-enhanced thermionic emission (PETE) is a new type of solar cell. The existing papers on PETE research do not consider the structure of actual PETE devices; in practical PETE structure, the original incident light intensity is attenuated by the window layer and the buffer layer (include anode in reflection PETE devices). In this paper, according to two kinds of the common structure of PETE device, the influence of transmission and reflection of sunlight on the conversion efficiency of PETE device is analyzed. Using a light-trapping structure on the cathode of the PETE device is a valid method to reduce the reflection of the incident light. The calculation results show that the optical attenuation has a great influence on the actual photon flux received by the cathode effective layer. Under the condition of reasonable operation of the device, the efficiency of PETE can be improved by reducing the size of the material, improving the light transmittance of the buffer layer and window layer, and using the light-trapping structure.